Bioactive Peptides from Edible Mushrooms—The Preparation, Mechanisms, Structure—Activity Relationships and Prospects - Haiyan Li; Ji’an Gao; Fen Zhao; Xinqi Liu; Biao Ma (Foods, 2023)
Mushroom bioactive peptides (MBPs) are bioactive peptides extracted directly or indirectly from edible mushrooms. MBPs are known to have antioxidant, anti-aging, antibacterial, anti-inflammatory and anti-hypertensive properties, and facilitate memory and cognitive improvement, antitumour and anti-diabetes activities, and cholesterol reduction. MBPs exert antioxidant and anti-inflammatory effects by regulating the MAPK, Keap1-Nrf2-ARE, NF-κB and TNF pathways. In addition, MBPs exert antibacterial, anti-tumour and anti-inflammatory effects by stimulating the proliferation of macrophages. The bioactivities of MBPs are closely related to their molecular weights, charge, amino acid compositions and amino acid sequences. Compared with animal-derived peptides, MBPs are ideal raw materials for healthy and functional products with the advantages of their abundance of resources, safety, low price, and easy-to-achieve large-scale production of valuable nutrients for health maintenance and disease prevention. In this review, the preparation, bioactivities, mechanisms and structure–activity relationships of MBPs were described. The main challenges and prospects of their application in functional products were also discussed. This review aimed to provide a comprehensive perspective of MBPs.